Study on the correlation of supplementation with L-citrulline on the gastrointestinal flora and semen antifreeze performance of ram - Fan, Chen; Aihemaiti, Aikebaier; Fan, Aoyun; Dilixiati, Airixiati; Zhao, Xi; Li, Zhuo; Chen, Changzheng; Zhao, Guodong (Frontiers in Microbiology, 2024)
Cryopreservation of semen can give full play to the reproductive advantages of male animals. However, in actual production, due to the poor frost resistance of sheep semen and the low conception rate, the promotion of sheep frozen semen is greatly hindered. Therefore, it is urgent to improve the frost resistance of semen to improve the quality of frozen semen. At present, most studies on improving the quality of frozen semen are based on the improvement of semen dilutions, and few studies on improving the freezing resistance of ram semen by feeding functional amino acids. Therefore, 24 Turpan black rams were divided into high antifreeze group (HF) and a low antifreeze group (LF) Each of these groups was further randomly divided into control and experimental subgroups. The control subgroup was fed a basal diet, while the experimental subgroup received an additional 12 g/d of L-Cit supplementation based on the control group for a duration of 90 days. The results showed that Following L-Cit supplementation, the experimental group demonstrated significantly elevated sperm density and VSL (Velocity of straight line), T-AOC, GSH-Px, and NO levels in fresh semen compared to the control group (P < 0.01). After thawing, the experimental group exhibited significantly higher levels of T-AOC, GSH-Px, and NO compared to the control group (P < 0.01). Additionally, the HFT group, after thawing frozen semen, displayed significantly higher HK1 protein expression compared to the control group. The number of spermatogonia, spermatocytes, and sperm cells in the HFT group was significantly higher than that in the HFC group. Moreover, 16S rRNA sequence analysis showed that Candidatus_Saccharimonas, Staphylococcus, Weissella, succinivbrionaceae_UcG_002, and Quinella were significantly enriched in the rumen of the HFT group, while Ureaplasma was significantly enriched in the HFC group. In the duodenum, Clostridiales_bacterium_Firm_14, Butyrivibrio, and Prevotellaceae_NK3831_group were significantly enriched in the HFT group, whereas Desulfovibrio and Quinella were significantly enriched in the HFC group. Under the conditions employed in this study, L-Cit supplementation was found to enhance the intestinal flora composition in rams, thereby improving semen quality, enhancing the antifreeze performance of semen, and promoting the development of testicular spermatogenic cells.